Digestible Valine Requirements for Maintenance in the Starting Turkey - Sun, S.; Brown, J.; Firman, J.; Kamyab, A.; McGill, E. (International Journal of Poultry Science, 2007)
The objective of these studies was to predict the valine requirement for maintenance in starting turkeys for use in a future modeling system. Amino acid requirement data can be determined in multiple fashions. One method for determining amino acid requirements is through modeling. A portion of the data required for a comprehensive model is the maintenance requirement. Two studies were conducted to determine the maintenance requirement for valine during the starter period for turkeys. Day-old poults (192 birds) were randomly assigned to pens to provide for six replications of eight treatments in two trials and a low protein diet was formulated so that different levels of valine could be fed to young turkeys. The maintenance requirements of valine were approximately 31 and 43 mg/bird/day in experiment 1 and experiment 2, respectively. This information, coupled with the amino acid requirements for growth, will allow for the construction of an effective model to predict amino acid requirements over a wide range of environmental and physiological conditions.